Recover the Historical and Ethnographic Legacy of Henri Pittier - Cruz Meléndez, Carlos (2018)
Henri Pittier is a scientist of Swiss origin, who performs an extensive and dilated research in Costa Rica in the late nineteenth and early twentieth century on fields like botany and geography. But it also ventures into areas of linguistics, ethnography and history. This essay seeks to show the importance that, in particular, for the social sciences, the recovery and study of this legacy has. For this purpose and as examples, I will comment on the relevance and pertinence of three essay or reports of the researcher where issues such as the longevity of the inhabitants of the region of Nicoya are addressed, the customs of indigenous peoples and their relationship with the State, or the process of the expansion of the Costa Rican national society towards the currently called “Zona Sur”.